Pengaruh Motivasi Intrinsik dan Motivasi Ekstrinsik Terhadap Produktivitas Kerja Pada PT. Az-Zuhra Property Pekanbaru - Safrizal Safrizal; Menhard Menhard; Muhammad Yusuf (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
The purpose of this study was to determine the effect of intrinsic motivation and extrinsic motivation on work productivity at PT. Az-Zuhra Properti in Pekanbaru, this research was conducted on employees of PT. Az-Zuhra Property in Pekanbaru. The type of research used is quantitative research. Sampling using saturated sampling technique, because the researchers only took samples of employee respondents, amounting to 35 respondents. Data collection techniques using questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression, classical assumption test, F hypothesis test, t hypothesis test, coefficient of determination. The results of the research conducted show that the coefficient of determination (adjusted R square) is 0.844 or 84.4%. That intrinsic motivation and extrinsic motivation simultaneously affect work productivity at PT. Az-Zuhra Property in Pekanbaru. Intrinsic motivation has no effect on work productivity at PT. Az-Zuhra Property in Pekanbaru. While extrinsic motivation partially affects the performance of employees at PT. Az-Zuhra Proerti in Pekanbaru. Keywords: Intrinsic Motivation, Extrinsic Motivation and Work Productivity